Cost Minimization Analysis Pasien JKN Rawat Jalan Penyakit Hipertensi di RS “X” Kota Surabaya - Kusuma Wardani, Deva Rahayu Nurindah; Amarullah, Adinugraha; Rahmawati, Dewi (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2023)
Background: Hypertension is a medical condition where there is an increase in blood pressure which can increase morbidity and mortality. Hypertension requires treatment for a long time and is relatively expensive. Aims: This study aims to describe the cost of antihypertensive therapy and to analyze the most cost-minimizing treatment for JKN outpatients with hypertension at